Kajian Hukum Islam Terhadap Teknologi Finansial Modern (Fintech): Tinjauan Fiqih terhadap Riba, Gharar, dan Maysir - Cindy Ayu Azhara; Nabila Zulfa Nur Latifa; Faris Fadhilah Zakiy; Much Yudi Firmansyah; Tegar Adi Nugraha; Muhammad Hakim Asshabi; Mirzam Arqy Ahmadi (Program Studi Hukum Ekonomi Syariah STAI As-Sunnah Deli Serdang, Sumatera Utara, 2025)
The development of financial technology (fintech) has provided greater ease in financial transactions for Muslim communities, yet it also raises challenges regarding compliance with Islamic principles. This study aims to explore the alignment of fintech services—such as e-wallets, online lending, digital investments, and cryptocurrencies—with Islamic law. Using a qualitative literature review approach, the research analyzes scholarly articles, fatwas, and relevant financial regulations. The findings indicate that many fintech services can be adapted to comply with Islamic law through the application of contracts such as murabahah, mudharabah, musyarakah, and qardhul hasan. Adaptive regulation and improved Islamic financial literacy are essential to ensure conformity with the objectives of Islamic law (maqashid al-shariah). The study recommends stronger collaboration among regulators, scholars, and industry stakeholders to build an inclusive and sustainable Islamic fintech ecosystem that promotes not only innovation, but also adherence to Islamic values.